2017
DOI: 10.4269/ajtmh.17-0365
|View full text |Cite
|
Sign up to set email alerts
|

Direct Biomarkers of Microbial Translocation Correlate with Immune Activation in Adult Zambians with Environmental Enteropathy and Hepatosplenic Schistosomiasis

Abstract: Abstract.Microbial translocation is a poorly understood consequence of several disorders such as environmental enteropathy (EE) and hepatosplenic schistosomiasis (HSS). Herein, we compared biomarkers of microbial origin and immune activation in adults with these disorders and in healthy controls. A cross-sectional study was conducted in participants with EE recruited from Misisi compound, Lusaka, Zambia; HSS patients and healthy controls from the University Teaching Hospital, Lusaka. Plasma lipopolysaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
1
10
2
Order By: Relevance
“…Additionally, contrary to previous studies ( Kaonga et al, 2017 ; Chabala et al, 2020 ), we found a male preponderance in this study (61.5%) probably due to the gender disparity that has been reported that women are less likely to participate in science and medicine ( Gayet-Ageron et al, 2019 ). In our study, at least two-thirds of HCPs believed individual variations can lead to different individual experiences with given medicines, similar to other studies ( Mahmutovic et al, 2018 ), which is important in the implementation of any PGx clinical care ( Muzoriana et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, contrary to previous studies ( Kaonga et al, 2017 ; Chabala et al, 2020 ), we found a male preponderance in this study (61.5%) probably due to the gender disparity that has been reported that women are less likely to participate in science and medicine ( Gayet-Ageron et al, 2019 ). In our study, at least two-thirds of HCPs believed individual variations can lead to different individual experiences with given medicines, similar to other studies ( Mahmutovic et al, 2018 ), which is important in the implementation of any PGx clinical care ( Muzoriana et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 99%
“…iFABP is an intracellular, mainly cytosolic protein of the enterocyte involved in long-chain fatty acid absorption 37 , which is released into the bloodstream by epithelial damage and is used as a biomarker of coeliac disease and environmental enteropathy 38 . LPS, a cell wall component of Gram-negative bacteria, is measured directly 39 using the Limulus amoebocyte lysate assay or indirectly using host-response molecules such as LBP and sCD14. These host molecules belong to the Toll-like receptor 4 complex on monocytes and macrophages, one of several LPS recognition systems 40 .…”
Section: Discussionmentioning
confidence: 99%
“…MT can exacerbate chronic inflammatory states, 49 including EED. 50 Biomarkers of MT include: lipopolysaccharide (LPS), a component of bacterial cell walls; the soluble LPS co-receptor CD14 (sCD14), which is upregulated by LPS; and antibodies to the core LPS core antigen (EndoCAb), which decrease after LPS binding ( Table 2). Multiple other biomarkers are available that measure derangements in multiple domains of pathology, including permeability, enterocyte injury, and mucosal and systemic inflammation ( Table 2).…”
Section: The Underlying Causes Of Eedmentioning
confidence: 99%